URGENSI TES PSIKOLOGI DALAM LAYANAN PENEMPATAN DAN PENYALURAN DI SMA - RAFSEL TAS'ADI (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
Placement and Distribution service is one of services that are provided in counseling. In senior high school level, this service is provided to place students to their relevant department. Previously, before psychological test was used, placing students into particular departments were only on the basis of their learning achievements. Consequently, higher achievement students were placed into natural science department while the lower ones were placed into social science one. Recently, due to the frequent uses of psychological test in recruiting employees and selecting new college entries, the test is also considered in helping school counselor to place their students into their appropriate department, both in terms of potential and academic achievements. It is expected that placing students into their appropriate any potential problems that the students might encounter in their study can be minimized.Kata kunci: tes psikologi, layanan penempatan dan penyaluran, penjurusan